A scoping review of evaluated interventions addressing developmental transitions for youth with mental health disorders. (6th December 2015) - Di Rezze, B.; Nguyen, T.; Mulvale, G.; Barr, N. G.; Longo, C. J.; Randall, G. E.
Abstract: Background: Youth with mental health disorders often experience challenges when transitioning into adult roles (e.g. independent living, work and community engagement). Health interventions that address the needs of youth with mental health disorders during these challenges in their development (i.e. developmental transitions) have not been reviewed in the literature. This scoping review examines the peer‐reviewed research that describes evaluated interventions addressing developmental transitions for youth with mental health disorders. Methods: A search of four prominent health literature databases (CINAHL, Embase, MEDLINE and PsycINFO) was conducted to identify evaluated developmental transition interventions for adolescents and youth (12–25 years) with mental health disorders. Study selection and analysis were guided by a methodological framework for conducting scoping reviews. Selected studies were described, assessed for quality and collated based on ten dimensions from two notable conceptual frameworks in developmental transitions and disability. Results: Nine studies met the inclusion criteria. The interventions within these studies demonstrated five specialized and four multi‐faceted programmes (i.e. multiple domains). All domains from the two conceptual frameworks were represented differently across studies. The sub‐domains from these studies were most frequently related to vocational‐focused interventions, least frequently related to social activities and living situation and did not explicitly map onto the sexuality sub‐domain. Three multi‐faceted interventions incorporated all domains and utilized each intervention approach. Study quality was rated for seven of the nine studies. Quantitative methodology for five of the seven studies was rated as higher quality. Conclusions: Evaluated interventions described in the transitions literature for youth with mental health disorders predominantly focus on vocational needs. The least studied areas were the personal and interpersonal domains. These domains were only incorporated within interventions addressing multiple domains of developmental transitions. These insights can be helpful in guiding evidence‐based practice and policy development, as well as informing gaps for future research programmes.